MOTIVASI, BUDAYA ORGANISASI DAN KINERJA APARATUR - Abbas, Azhar (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Motivation, Organizational Culture and Performance Apparatus. The purpose of this study was to determine the influence of organizational culture on the motivation and performance of the apparatus Keritang Indragiri Hilir Subdistrict. The study population was all employees of Head Office Curly many as 27 people and all the employees sampled. Data collection techniques were questionnaires and interviews. The research method used is quantitative analysis. This research was multiple regression see health effects of motivation and organizational culture on performance. From the research results show that the alternative hypothesis (H1) is accepted that a significant difference between the free variable motivation (X1) against the performance dependent variable (Y). Furthermore, there is a negative and significant influence of organizational culture on performance. It can be seen that the regression between motivation (X1) and organizational culture (X2) on the performance (Y) simultaneously produce the coefficient of determination (R ²) of 0.430. This means that the influence of motivation (X1) and organizational culture (X2) simultaneously on the performance (Y) is approximately 43% while the rest influenced by other factors.